(untitled) (Mongolian Journal of Agricultural Sciences, 2015)
Brown adipose tissue in newborn lambs accounts for 4.52% of total body weight, then during postpartum period it intensively decreases, reaching 1.5% after a week, and finally it is gradually adsorbed or replaced with white adipose tissue. Fatty acids composition of lamb brown adipose tissue includes 17 unsaturated fatty acids (53.23%) and 11 saturated ones (46.95%). Mongolian Journal of Agricultural Sciences Vol.15(2) 2015; 38-42